2009
DOI: 10.1007/s00104-009-1754-4
|View full text |Cite
|
Sign up to set email alerts
|

Altersappendizitis

Abstract: The CRP value showed a strong correlation with respect to the grade of inflammation and perforation. In conclusion, elderly patients with symptoms of appendicitis and a CRP value higher than 102 mg/l should undergo early diagnostic laparoscopy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
7
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 24 publications
1
7
0
Order By: Relevance
“…However, both CRP and WBC may be less useful for making a decision as to the treatment [46]. The comparisons of CRP and WBC between the groups in this study were consistent with the results reported earlier, where CRP correlated best with the severity of appendicitis [23,47,48,49]. Even though CRP takes approximately 24 h to peak, it has been discussed as a marker indicating when surgery is the optimal choice of treatment [50].…”
Section: Discussionsupporting
confidence: 82%
“…However, both CRP and WBC may be less useful for making a decision as to the treatment [46]. The comparisons of CRP and WBC between the groups in this study were consistent with the results reported earlier, where CRP correlated best with the severity of appendicitis [23,47,48,49]. Even though CRP takes approximately 24 h to peak, it has been discussed as a marker indicating when surgery is the optimal choice of treatment [50].…”
Section: Discussionsupporting
confidence: 82%
“…According to some studies [13], a high CRP value in elderly patients with acute appendicitis, could be a suspect index for the existence of a perforation (AUC 0.811 with the cut-off of 101.9 mg/l). Shin et al showed, as the delta neutrophil index, that measures of the fraction of immature granulocytes in the circulation is the only independent marker that can significantly predict the presence of perforation in multiple regressions in elderly patients [36].…”
Section: Have Laboratory Tests Sufficient Diagnostic Accuracymentioning
confidence: 99%
“…12 Department of Emergency Medicine, Morgagni-Pierantoni Hospital, Forlì, Italy. 13 Department of Biochemical Sciences and Human Oncology, University of Medical School "A. Moro" of Bari, Bari, Italy. 14 General and Oncological Surgery, Filippo Neri Hospital, Rome, Italy.…”
Section: Availability Of Data and Materials Not Applicablementioning
confidence: 99%
See 1 more Smart Citation
“…Laboratory data show that serum levels of the white blood cell (WBC), C-reactive protein (CRP), and interleukin-6 are related to AA[ 44 - 46 ]. The most reliable marker is neither the neutrophil count nor CRP, but the WBC count[ 1 , 44 ].…”
Section: Diagnostic Valuementioning
confidence: 99%